Impact of diffusion methods and metal cations on photochromic three-component D–A hybrid heterostructures. Issue 35 (27th August 2020) - You, Ming-Hua; Li, Meng-Hua; Liu, Jing-Yan; Lin, Mei-Jin
Abstract : Four three-component D–A hybrid heterostructures have been obtained and the impacts of metal cations contained and diffusion methods used on their structures as well as photochromic properties have been discussed. Abstract : D–A hybrid heterostructures are an attractive class of hybrid complexes composed of semiconducting organic and inorganic components, which make them potential candidates for applications in the photoelectric fields, particularly as photochromic materials. Herein, we report that the combination of metal cations (M = Zn 2+ or Cd 2+ ), silicomolybdic anions, and N, N -di(4-pyridyl)-1, 4, 5, 8-naphthalene diimide (DPNDI) via two diffusion methods (A and B) led to four three-component D–A hybrid heterostructures with silicomolybdic anions as electron donors, and one-dimensional (1-D) naphthalenediimide coordination networks of different metal cations, [Zn2 (DPNDI)2 (H2 O)4 ]·(SiMo12 O40 ) (1-A and 1-B ) and [Cd2 (DPNDI)2 (H2 O)4 ]·(SiMo12 O40 ) (2-A and 2-B ), as electron acceptors. Although the different diffusion methods, 1-B, 2-A and 2-B, are isostructures with close cell parameters. Due to the different ionic radii and electronegativity of metal cations in isostructural 1-B and 2-B, they exhibit different electron-transfer photochromic behaviors. This study paves a new path for designing novel photochromic materials through such third-component metal cations.